Characterisation of cefiderocol-non-susceptible Acinetobacter baumannii isolates from Taiwan. (March 2022) - Yamano, Yoshinori; Ishibashi, Naoki; Kuroiwa, Miho; Takemura, Miki; Sheng, Wang-Huei; Hsueh, Po-Ren
Highlights: Avibactam decreased the cefiderocol (CFDC) MIC against CFDC-resistant Acinetobacter baumannii . Among 21 CFDC-resistant A. baumannii, the PER ESBL was identified in 1 isolate. Among 21 CFDC-resistant A. baumannii, iron transporter PiuA deficiency was observed in 13 isolates. ABSTRACT: Objectives: Cefiderocol (CFDC), a siderophore cephalosporin, is active against Gram-negative bacteria including carbapenem-resistant Acinetobacter baumannii (CRAB). In this study, 100 CRAB isolates from patients with bacteraemia in Taiwan were characterised, among which 21 CFDC-non-susceptible isolates were identified with a minimum inhibitory concentration (MIC) of ≥8 mg/L. Methods: The effect of avibactam on CFDC activity was evaluated using broth microdilution methods according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Whole-genome sequencing (WGS) was performed on all CFDC-non-susceptible isolates (MIC ≥ 8 mg/L) for multilocus sequence typing (MLST) analysis, possession of β-lactamase genes and identification of possible variations in the PiuA iron transporter. Results: Addition of avibactam, a diazabicyclooctane inhibitor for serine-type β-lactamases, resulted in a ≥8-fold decrease in the CFDC MIC for 15 of 21 CFDC-non-susceptible isolates compared with only 1 of 79 CFDC-susceptible isolates (MIC ≤ 4 mg/L). WGS analysis confirmed that all CFDC-non-susceptible isolates harboured multiple β-lactamases including ADC-30 homologues, OXA-23 and OXA-66. One isolate with a high MIC (>32 mg/L) had a PER-type extended-spectrum β-lactamase (ESBL) gene. Twenty other isolates belonged to ST455, ST473 and ST787. Among these, thirteen ST455 isolates were deficient in PiuA, a siderophore uptake receptor that may be required for optimal penetration of CFDC. Conclusion: MICs of CFDC-non-susceptible CRAB isolates from Taiwan could be significantly decreased to susceptible levels by the addition of avibactam, suggesting the involvement of β-lactamases in resistance. Among the 21 CFDC-non-susceptible isolates, 1 isolate had a PER-type ESBL gene and 13 isolates lacked a PiuA iron siderophore transporter.